1983
DOI: 10.2170/jjphysiol.33.391
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ketamine on renal nerve activity, arterial pressure and heart rate in rats.

Abstract: We recorded renal nerve activity (RNA) together with arterial pressure (AP) and heart rate (HR) in 24 Wister rats anesthetized with nitrous oxide to investigate the effects of ketamine on the sympathetic nerve activity and the cardiovascular dynamics. The magnitude and time course of the responses to four graded doses of ketamine (1, 5, 10, 25 mg/ kg) were studied in 19 rats. RNA responded biphasically, initially decreasing dose-dependently to minimal values of 89±4.4, 77±8.2, 54±5.2, and 17±3.7% of control fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The magnitude of changes observed in these parameters after injections were larger in animals administered the 25.0 mg kg -1 dose of ketamine than in those administered 12.5 mg kg -1 . These results support previous findings showing that ketamine modulated, in a dosedependent manner, low-and high-frequency EEG components [10,11] as well as the activities of cardiac [12,13] and respiratory [14,15] neural networks. The transient changes observed in cortical, cardiac, respiratory, and digastric EMG activities after ketamine injections returned to pre-injection levels at the onset of RJMs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The magnitude of changes observed in these parameters after injections were larger in animals administered the 25.0 mg kg -1 dose of ketamine than in those administered 12.5 mg kg -1 . These results support previous findings showing that ketamine modulated, in a dosedependent manner, low-and high-frequency EEG components [10,11] as well as the activities of cardiac [12,13] and respiratory [14,15] neural networks. The transient changes observed in cortical, cardiac, respiratory, and digastric EMG activities after ketamine injections returned to pre-injection levels at the onset of RJMs.…”
Section: Discussionsupporting
confidence: 92%
“…The anesthetic effects of ketamine on central nervous system functions are attributed to the blockade of N-methyl-D-aspartate (NMDA) receptors [9]. Previous studies report that ketamine injections cause changes in cardiorespiratory activities (i.e., heart rate or respiratory rate) as well as the emergence of cortical electroencephalographic (EEG) activities (i.e., delta EEG activity and sleep spindles) during NREM sleep; these effects showed a gradual change with time after the injection [10][11][12][13][14][15]. Such findings suggest that cortical, cardiac, and respiratory activities reflect specific vigilance states that are essential for generating RJMs after ketamine injections.…”
Section: Introductionmentioning
confidence: 99%
“…The rectal temperature of the animals was maintained at about 38°C with a heating lamp. The method of renal nerve dissection was similar to that described in a previous paper (SHIRAHATA et al, 1983). Renal nerve activity (RNA) was recorded from the cut central end of the multifiber strands with bipolar silver-silver chloride electrodes.…”
Section: Methodsmentioning
confidence: 99%
“…A different anesthesia may lead to differences in the reduction of blood pressure and reflex activation of the sympathetic nervous system and the renin angiotensin system. To anesthetize rats in the present study, we used ketamine, which has been shown to produce biphasic responses to renal sympathetic nerve activity (RSNA) [33] or increase RSNA [34]. A prejunctional action to enhance noradrenaline release from sympathetic nerve terminals contributes to the ability of AngII to enhance reduction in total renal blood flow induced by renal nerve stimulation [35], so a similar mechanism may also operate in medullary circulation [13].…”
Section: Role Of T-type Calcium Channel On Angiiinduced Responses Of mentioning
confidence: 99%